La adopción homo parenteral y el Derecho Comparado, consideraciones para su reconocimiento en Ecuador. - Llanos García, Renata Valeria (2022)
This research focuses on the normative and doctrinal analysis on the legal institution of homo parental adoption in Comparative Law as a valid precedent for its incorporation and approval in Ecuador, considering the normative contradictions and legal gaps existing within our legal system , with respect to this type of adoption, which originates discriminatory acts, which violate the rights of both couples made up of people of the same sex, as well as children and adolescents who are capable of being adopted. The research carried out is of a basic type, bibliographic, field, and descriptive documentary, with a non-experimental design, carried out with a sample of 25 people involved. The survey used as a data collection technique and the questionnaire as an instrument, which has made it possible to establish the level of social acceptance that homo-parental adoption has in our country and its impact on recognition within the legal system. Hence, at the conclusion of the investigation, it determined that the recognition of homo parental adoption is a reality that has been included in the Constitutions and regulations of many countries today, allowing the full exercise of the rights of homosexual people who wish to access this legal institution, giving them possibilities and variations to those already established with respect to it, hence, scientifically in many countries where homo parental adoption has been legalized, it has been shown that there is no type of affectation in the minors who are part of these families through adoption, which has led to the establishment of valid and significant criteria with normative and doctrinal support that will contribute to the analysis of the importance of the recognition of homo parental adoption in Ecuador.